The Demoscene: from digital subculture to UNESCO intangible cultural heritage. - Furman, Ivo; Erdikmen, Arda (International Journal of Heritage Studies, 2026)
The Demoscene is a transnational digital culture that, since the 1980s, has fused programming, artistic experimentation, and community collaboration in the production of 'demos', short audiovisual programs designed to push hardware and software to their limits. Emerging from the intertwined worlds of home computing and software piracy, it developed into a semi-autonomous field of cultural production governed by its own hierarchies, evaluative logics, and forms of capital. Drawing on Pierre Bourdieu's theory of cultural fields, this article traces the Demoscene's evolution from exclusionary elite – lamer distinctions towards more inclusive practices that continue to prize technical, aesthetic, and social capital. It then considers the 2019 Art of Coding initiative, an effort to secure UNESCO intangible cultural heritage recognition, as a key episode that illustrates how community outreach actors bridged the Demoscene's peer-driven values with institutional frameworks. While UNESCO recognition introduces symbolic capital that enhances the scene's visibility and legitimacy within cultural and heritage sectors, it also provokes ambivalence among participants who fear that external validation may erode grassroots autonomy. The article argues that the Demoscene exemplifies how digital subcultures negotiate institutional recognition, showing that heritage frameworks can expand visibility and protection without displacing the peer-driven logics of distinction that sustain them.